2013
DOI: 10.1186/1472-6963-13-480
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in Southern Ethiopia: distribution, rates and determinants of service provision

Abstract: BackgroundCataract is the leading cause of blindness worldwide, with the greatest burden found in low-income countries. Cataract surgery is a curative and cost-effective intervention. Despite major non-governmental organization (NGO) support, the cataract surgery performed in Southern Region, Ethiopia is currently insufficient to address the need. We analyzed the distribution, productivity, cost and determinants of cataract surgery services.MethodsConfidential interviews were conducted with all eye surgeons (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
0
30
0
2
Order By: Relevance
“…For instance, one study in Ethiopia found that the productivity of NPCSs (CSs per surgeon per year) was 280 compared to 682 for ophthalmologists in the same area. 21 Similarly, task shifting of trichiasis surgery for trachoma to general healthcare workers began in 2007, but the median number of surgeries per surgeon was again lower than anticipated. Inadequate surgical output is likely due to the lack of support for outreach, a dearth of supplies, including instruments and consumables, and inadequate supervision.…”
Section: Barriers To Implementing Care In Ssamentioning
confidence: 99%
“…For instance, one study in Ethiopia found that the productivity of NPCSs (CSs per surgeon per year) was 280 compared to 682 for ophthalmologists in the same area. 21 Similarly, task shifting of trichiasis surgery for trachoma to general healthcare workers began in 2007, but the median number of surgeries per surgeon was again lower than anticipated. Inadequate surgical output is likely due to the lack of support for outreach, a dearth of supplies, including instruments and consumables, and inadequate supervision.…”
Section: Barriers To Implementing Care In Ssamentioning
confidence: 99%
“…Lastly, a cortical cataract is identified by the present of white, wedge-like opacities in the periphery which later converge to the centre of the lens. This type of cataract occurs in the lens cortex, which is the part of the lens that surrounds the central nucleus 7 .…”
Section: Type Of Cataractmentioning
confidence: 99%
“…Issues include ability to pay, 42; 150; 230; 267 adherence to treatment, 41 access to follow up, 85; 143, and provision of medical staffing and equipment. 87 Additionally there are over-arching risk factors affecting all domains of health care including environmental, cultural 264 and geopolitical issues. 219…”
Section: B the Problem Of Deprivationmentioning
confidence: 99%